Framework for Orienting Engineering Undergraduate Final Year Projects towards New Product Innovation Process - Ammar, Al-Shalabi; S. B., Chee; Narish, Singh; B. F., Yousif (2008)
The traditional framework, for undergraduate final year project (FYP) has customarily focused oil the sharpening of theoretical principles and the honing of fundamental practical skills. This work sees the pressing need for orienting FYPs at the undergraduate level towards new product innovation. Hence, an unconventional framework, incorporating new product development (NPD) processes and practices, is created, aiming to generate more balanced and productive graduates; and enabling them to contribute to the NPD innovation process. For the purpose of comparison, the traditional FYP framework is firstly introduced. Then. each phase in the new framework, which embodies the actual activities carried out in a customer-oriented organization, is presented in detail. In addition to that, a project was developed and the proposed framework, was implemented. As a result. a potential was found for the new developed framework.